A Rare Case Report Of Right Temporal Solitary Fibrous Tumor In A Young Adult - N, Sriram.; A.D, Dharshini; Dheenadhayalan, M.; Karthickeyan, K.; Shanmugasundaram, P.; Sri, M. K. Sundar (Journal of Neonatal Surgery, 2025)
Solitary fibrous tumours (SFTs) which was previously classified under hemangiopericytomas (HPF) are rare mesenchymal neoplasms that may arise within the cranium. This case describes a 19-year-old male who presented with persistent headache and was diagnosed with an extra-axial right Fronto-temporal SFT. Followed by preoperative embolization the patient under went right frontotemporal craniotomy with subtotal tumour excision. Here, a extremely rare case report of young adult diagnosed with hemangiopericytomas with post right frontotemporal craniotomy and subtotal excision of solitary fibrous tumour.